Górny Śląsk - przypadek szczególnego pogranicza = Upper Silesia - the case of a special borderland - Kosmala, Gerard; Spallek, Waldemar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
For centuries Upper Silesia was a borderland between Polish and German national ecumenes. As a political periphery, Upper Silesia became the key economic region in the 19th century. After World War II this region became a part of Poland and was subjected to various forms of political activity.
Keywords: Górny Śląsk; historia; pogranicze